Diversidade Genética e estrutura espacial intrapopulacional em Tibouchina papyrus(POHL) Toledo utilizando marcadores microssatélites. - LIMA, Jacqueline de Souza (2011)
Tibouchina papyrus is a Melastomataceae endemic to the Cerrado. It has a disjunct distribution, restricted to campos rupestres . Therefore, it can be considered a model species, helping guide Cerrado endemic plant studies. Thus, this study aimed to characterize genetic variability in microsatellite regions of T. papyrus genome and use spatial statistical analysis methods to assess genetic diversity and structure in disjunct populations. Individuals were georeferenced and leaf samples were taken from the localities of Serra dos Pirineus (216), Serra Dourada (66) and Serra de Natividade (192). In order to obtain the genotypes, we used ten microsatellite loci that were developed for T. papyrus. The locus showed a mean of 3,4 alleles and a large number of private alleles was detected (19 in total) at the populations studied. Values (f) significant were observed for two populations, indicating that populations not are following the proportions expected by Hardy-Weinberg. The global  value is significant and equal to 0.712, showing a high differentiation among the three populations studied. Thus, the three populations of T. papyrus can be treated as three different ESUs. Spatial genetic structure was weak for two populations, with low levels of SP. The low SGS corroborates the hypothesis that wind-dispersed species present no SGS due to long distance gene flow because of seed dispersal. This is plausible for T. papyrus, which is a wind-dispersed species. Despite the low intra-population SGS found in two populations, based on the relationship between kinship and distance, significant positive values were observed for the some distance class, indicating higher values for the relationship between these individuals. The intercept of the correlogram for each population may indicate the minimum distance where it is more likely that sampled individuals are less similar, which is an information applicable for the management of T. papyrus populations. Based on genetic data, it was evident that the three T. papyrus populations must be preserved, because each one contains a number of unique genetic variability that is not shared between them. Thus, theoretically it is possible to maintain the evolutionary potential of this species and to avoid local extinction in only three regions where it occurs.